Kajian Literatur Adopsi Cloud Computing pada UMKM : Perspektif Strategis dan Dinamika dalam Satu Dekade - Ruslaini Ruslaini; Eka Wahyu Kasih; Seger Santoso (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
This study examines the adoption of cloud computing in Small and Medium Enterprises (SMEs) with a focus on analyzing trends, theories, and factors influencing adoption during the period from 2011 to 2020. Using a systematic literature review approach, this research analyzes 76 articles published during this period, aiming to provide a deeper understanding of data analysis techniques, cloud computing services commonly studied, and key factors driving or hindering adoption. The findings reveal that the most frequently used analysis techniques are Partial Least Squares Structural Equation Modeling (PLS-SEM) and interpretative analysis. The most analyzed cloud computing service is Software as a Service (SaaS), while the primary factor driving adoption is cost savings. This study also identifies that the majority of studies are not based on clear theoretical frameworks, and research has been predominantly focused in the Asian region. The findings offer insights for future research on developing cloud computing implementation in SMEs, as well as factors to consider in accelerating the adoption of this technology among SMEs globally.